Significance of development with regard to takeover of life roles among persons with mild intellectual disability - Valaikienė , Aistė (Social Welfare: Interdisciplinary Approach, 2015)
The school plays an important role in preparation of persons with mild intellectual disability to adult's life. A person who starts his/ her independent life, usually experiences a shift in three general roles at work, in recreational activity and in socialization. An in-depth interview was conducted among persons with mild intellectual disability at the age of 18-33 in Lithuania and Italy in 2012-2013, in order to reveal the structure of takeover of life roles and the significance to success related to the participation in labour market. The successful structure of takeover of life roles among persons with mild intellectual disability along with the prerequisites for its formation and the significance to occupational integration are analysed in the current article. The article emphasizes the importance of prevocational education in formation of skills with regard to takeover of life roles.
Keywords: persons with mild intellectual disability; prevocational education; occupational integration; life roles